Model of implementing proficiency testing in Vietnam, a developing country - Hy Triet Van; Van Thanh Tran; Manh Tuan Ha; Quang Huy Vu (Practical Laboratory Medicine, 2023)
Backgrounds and aims: The aim of this study is to provide a good approach for a quantitative EQA scheme assigned value with limited resources. Materials and methods: Twelve lyophilized EQA items were distributed to participants in 2021 from North to Southeast Vietnam to measure the concentration of nine parameters, including glucose, urea, creatinine, cholesterol, triglyceride, uric acid, AST, ALT, and GGT. The consensus value of the expert group and all participants were calculated and statistically compared to choose the most appropriate consensus value. Results: Fifty-nine laboratories attended the EQA scheme, including an expert group using automatic biochemistry analyzers (AAs) and all participants with auto and semi-auto biochemistry (SAA) analyzers. Consensus values of six per nine parameters were different between the two groups for at least two EQA items, including glucose, creatinine, cholesterol, uric acid, AST, and ALT. The coefficients of variation of glucose, urea, creatinine, triglycerides, uric acid, and GGT in the expert group were significantly lower than those in all the participants. Conclusion: Using the consensus values of expert groups as the assigned values of the EQA program is a relevant strategy to increase testing quality in developing countries with limited resources, such as Vietnam.